Developing Video-Based English Textbook for Elementary School Students - Monika Widyastuti Surtikanti (Journal of English Language Teaching and Islamic Integration, 2019)
In the Curriculum 2013, English is excluded from the Elementary School Subjects, especially for the State Elementary Schools. Some private elementary schools keep teaching English to their students. One of them is SD Kristen Widya Wacana Jamsaren. The English teachers found difficulty in providing a textbook that covers the students’ need. This is a Research and Development (R & D) study which conducts the preliminary survey, designing and developing the prototype of the product, conducting limited testing and product validation, having a revision process and describing the research result. This study is aimed at finding out the students’ need and providing a video-based textbook to teach English for the sixth grade students of SD Kristen Widya Wacana Jamsaren. The video-based textbook is developed based on the need analysis, syllabus and some theories related to teaching English to young learners.